# math

posted by .

If f(x)= x^2-4 and g(x)= 2x-7

Find
a) f(g inverse(x))
b) g((g)inverse(x))

## Similar Questions

1. ### inverse

find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2, x <= 2 how do I solve this problem?
2. ### Pre-Calc

Does y=1/x have an inverse? It is a one-to-one function, so it should be the inverse equation is the same?
3. ### Inverse of log function

Find the inverse of f(x) = log(2+x) - 4 the base is "a" Call f(x) y y = loga(2+x) -4 y+4 = loga(2+x) a^(y+4) = 2 + x x = a^(y+4) - 2 drwls, you have merely solved the equation for x. The question was to find the "inverse", so the actual …
4. ### algebra

1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). Use finite differences to determine the equation of the function. (b) Draw the graph of the function. (c) Draw the inverse on the graph. (d) Show at least two different …
5. ### math

The cost of producing q articles is given by the function C=f(q)=100+2q. (A) Find the formula for the inverse function. (B) Explain in practical terms what the inverse function tells you. I am pretty sure the answer to A is f^-1(C)=C/2-50 …
6. ### Algebra

what is the inverse of the linear parent function?
7. ### Pre-caluclus

I do not know how to solve for y to get the inverse of this question: The number of elephants in a park is estimated to be P(t)=7500 1 + 749e^(−0.15t) where t is the time in years and t = 0 corresponds to the year 1903. Find …
8. ### Advanced Algebra

What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case, give …
9. ### Math

Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to 2). First prove that f(x) is one to one in the defined domain of f and then obtain the inverse function. I know how to find the inverse. We just switch x and …
10. ### Math- steve? reiny?

1. Let f(x)=x^5 + 2x^3 + x - 1 Find f^-1(3) and (f^-1)'(3)?

More Similar Questions